A study on the influence of social media marketing activities on brand awareness of iPay88 (M) Sdn Bhd/ Siti Aishah Mohd Nor - Mohd Nor, Siti Aishah (2018)
The new ways for companies and brands to market their products and services have been available with the existence of social media. There is insufficient evidence on how the social media marketing activities influence brand awareness, especially in Malaysia. Therefore, this research wants to investigate the social media marketing activities that influence brand awareness. This study adapted the framework that has been developed by previous researchers by classifying social media marketing activities as entertainment, customization, trendiness and perceived risk. The researcher discards one of the independent variable which is interaction that was initially part of the social media marketing activities in the framework as a multicollinearity problem demand that correction be made to get a more reliable result. The questionnaires are distributed online through WhatsApp, Facebook and Twitter to 110 respondents who follow iPay88's social media page. The result of this study is analyzed by using Statistical Package for Social Sciences (SPSS). By having an understanding on the influence of social media marketing activities on brand awareness, iPay88 would be able to create a new marketing strategy and focus more on the activities that could help them to make people aware of the brand.